Prognostic significance of osteopontin in patients with lung cancer: a meta-analysis - Peng, Bin (Int J Clin Exp Med, 2014)
Both plasma/serum/pleural effusion osteopontin concentration (PSPO) and tumor tissue osteopontin expression (TTO) have recently been reported to be involved in the prognosis of lung cancer. In this study, we performed a meta-analysis to demonstrate the association between PSPO/TTO and survival in patients with lung cancer. We searched in PubMed, EMBASE, Cochrane library, Web of Science and Chinese Biomedical database (CBM) for relevant literatures. Stata 12.0 was applied to pool the eligible studies and synthesize hazard ratios (HRs) and its corresponding 95% confidence interval (CI). For PSPO, a total of 8 studies with 1000 patients were included in final analysis. Combined HR suggested high PSPO predicted an unfavorable overall survival (OS) (HR=1.52, 95% CI: 1.13-2.05) and progress-free survival (PFS) (HR=1.73, 95% CI: 1.35-2.21). For TTO, 5 studies with a total of 747 patients were employed in final analysis. Pooled HR indicated that elevated TTO was associated with poor OS (HR=2.16, 95% CI: 1.65-2.83) and disease/relapse-free survival (D/RFS) (HR=2.36, 95% CI: 1.79-3.12). Subgroup analysis was performed to explore the causes of heterogeneity. Publication bias by begg’s test was not statistically significant. Sensitivity analysis showed that the pooled results were robust. This study revealed that both high TTO and PSPO are associated with poor prognosis in patients with lung cancer.